Platelets: "multiple choice" effectors in the immune response and their implication in COVID‐19 thromboinflammatory process. (22nd March 2021) - Rolla, Roberta; Puricelli, Chiara; Bertoni, Alessandra; Boggio, Elena; Gigliotti, Casimiro Luca; Chiocchetti, Annalisa; Cappellano, Giuseppe; Dianzani, Umberto
Abstract: Although platelets are traditionally recognized for their central role in hemostasis, the presence of chemotactic factors, chemokines, adhesion molecules, and costimulatory molecules in their granules and membranes indicates that they may play an immunomodulatory role in the immune response, flanking their capacity to trigger blood coagulation and inflammation. Indeed, platelets play a role not only in the innate immune response, through the expression of Toll‐like receptors (TLRs) and release of inflammatory cytokines, but also in the adaptive immune response, through expression of key costimulatory molecules and major histocompatibility complex (MHC) molecules capable to activate T cells. Moreover, platelets release huge amounts of extracellular vesicles capable to interact with multiple immune players. The function of platelets thus extends beyond aggregation and implies a multifaceted interplay between hemostasis, inflammation, and the immune response, leading to the amplification of the body's defense processes on one hand, but also potentially degenerating into life‐threatening pathological processes on the other. This narrative review summarizes the current knowledge and the most recent updates on platelet immune functions and interactions with infectious agents, with a particular focus on their involvement in COVID‐19, whose pathogenesis involves a dysregulation of hemostatic and immune processes in which platelets may be determinant causative agents.